Growth and development of bulls of different types of productivity - Donetskikh Alexandr (EDP Sciences, 2021)
The article provides data on the weight growth of bulls of different types of productivity. The growth and development of Black-and-white, Simmental and Aberdeen-Angus bulls were studied during the period of their rearing and feeding. The change in live weight was established, the dynamics and growth rate of the studied bulls were calculated depending on the breed and type of productivity. The research results showed that the Aberdeen-Angus bulls had the highest live weight during fattening - 485.2 kg, which was significantly higher than that of the Black-and-White and Simmental breeds by 68.7 kg (p <0.001) or 14.0% and 19.7 kg (p <0.01), or 4.1% respectively. The average daily gain in live weight from birth to 15 months of age in bulls of Black-and-white, Simmental and Aberdeen Angus breeds amounted to 860.0; 965.1 and 1022.7 grams respectively. In the Aberdeen-Angus cattle, in comparison with the Black-and- White and Simmental breeds, the value of this indicator was significantly higher, by 162.7 g, or 15.9% (p <0.001) and 57,6 g, or 5.6% (p <0.01) respectively. It was found that the type of productivity had a certain effect on the dynamics of live weight, the intensity of growth and development of animals.